Respuesta :

Answer:

The solution to the system of equations will be:

[tex]x=9,\:y=6[/tex]

Step-by-step explanation:

Given the system of equations

[tex]\begin{bmatrix}2x-9y=-36\\ -14x+18y=-18\end{bmatrix}[/tex]

Multiply 2x-9y=-36 by 7

[tex]14x-63y=-252[/tex]

so the system of equations becomes

[tex]\begin{bmatrix}14x-63y=-252\\ -14x+18y=-18\end{bmatrix}[/tex]

Adding both equations

[tex]-14x+18y=-18[/tex]

[tex]+[/tex]

[tex]\underline{14x-63y=-252}[/tex]

[tex]-45y=-270[/tex]

solve -45y = -270 for y

[tex]-45y=-270[/tex]

divide both sides by -45

[tex]\frac{-45y}{-45}=\frac{-270}{-45}[/tex]

Simplify

[tex]y=6[/tex]

For 14x-63y = -270 plug in y = 6

[tex]14x-63\cdot \:6=-252[/tex]

[tex]14x-378=-252[/tex]

Add 378 to both sides

[tex]14x-378+378=-252+378[/tex]

Simplify

[tex]14x=126[/tex]

Divide both sides by 14

[tex]\frac{14x}{14}=\frac{126}{14}[/tex]

Simplify

[tex]x=9[/tex]

Therefore, the solution to the system of equations will be:

[tex]x=9,\:y=6[/tex]